Study of Adenosine Deaminase Activity As A Biochemical Marker of Cell Mediated Immunity in Tuberculous Meningitis, Tuberculous Pleural Effusion and Tuberculous Ascites (Journal of Medicine, 2012)
The present study conducted with the aim that ADA estimation is a simple cheaper and quicker biochemical test and could provide additional supportive evidence for the diagnosis of tuberculous meningitis, tuberculous pleural effusion, tuberculous ascites in clinically suspected cases and will therefore help in early institution of therapy to these patients. The data was collected and interpreted at department of Physiology and Department of Medicine Gandhi Medical College, Bhopal.DOI: http://dx.doi.org/10.3329/jom.v13i1.9065JOM 2012; 13(1): 32-38